Contribution Of Parents and Leadership Of Village Community Towards The Implementation Of Independent Pai Curriculum At MTSN 1 Padangsimpuan - Putri, Indah Rahmadani; Syafnan (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
This study analyzes the contribution of parents and educated village community leaders in the implementation of the PAI Merdeka Curriculum at MTsN 1 Padangsidimpuan. A qualitative method with a case study approach was used through observation and literature review. The results show that parents play a role in learning motivation, providing facilities, and strengthening religious values, while community leaders support curriculum socialization, dialogue facilitation, and religious programs. Collaboration between these parties is the key to the successful implementation of the PAI Merdeka Curriculum.